2009
DOI: 10.1007/s00403-009-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

Gingko biloba extract reduces VEGF and CXCL-8/IL-8 levels in keratinocytes with cumulative effect with epigallocatechin-3-gallate

Abstract: In skin inflammation, vascular endothelial growth factor (VEGF) and CXCL-8/IL-8 play an important role and are produced by activated keratinocytes. Extracts from Ginkgo biloba leaves (GBE), widely used in phytotherapy, have been reported to exert antioxidant and anti-inflammatory properties in the skin. We therefore evaluated the effects of GBE on the release of VEGF and CXCL8/IL-8 by normal human keratinocytes (NHKs) activated by tumor necrosis factor alpha (TNFalpha). Moreover, as we previously showed that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Ginkgo biloba (GB) has been used in traditional Chinese medicine for about 5000 years, and it is one of the herbal drugs that is used widely according to its antioxidant properties and ability to modify vasomotor function, affect ion channels to inhibit activation of platelets and smooth muscle cells [14], stimulate neurotransmitters [15], decrease adhesion of blood cells to endothelium, and modify signal transduction [14]. In addition, GB has been used in the treatment of Alzheimer's disease and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgo biloba (GB) has been used in traditional Chinese medicine for about 5000 years, and it is one of the herbal drugs that is used widely according to its antioxidant properties and ability to modify vasomotor function, affect ion channels to inhibit activation of platelets and smooth muscle cells [14], stimulate neurotransmitters [15], decrease adhesion of blood cells to endothelium, and modify signal transduction [14]. In addition, GB has been used in the treatment of Alzheimer's disease and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Other agents, include trypsin, which increases and salbutamol, which inhibits the production of IL-8 from keratinocytes (14). Gingko biloba extract also inhibits IL-8 secretion from keratinocytes (15). IL-8RA and IL-8RB have been found to be present in keratinocytes of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Two processes may lead to blood vessel production: vasculogenesis and angiogenesis. Both the promotion and the reduction of angiogenesis have been reported with the use of GBE (Sun et al, 2009;Trompezinski et al, 2010). Sun et al (2009) reported that the GBE exerts protective effect on secondary cerebral ischemic injury after Sub Arachnoids Hemorrhage via the promotion of the expression of VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…Sun et al (2009) reported that the GBE exerts protective effect on secondary cerebral ischemic injury after Sub Arachnoids Hemorrhage via the promotion of the expression of VEGF. On the other hand, Trompezinski et al (2010) showed that GBE exerts a potent inhibition on VEGF levels in activated cells. GBE down regulates VEGF and IL-8 (interleukin 8) levels in a cumulative manner in Tumor necrosis factor-α (TNFα)-stimulated normal human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation